Enhancement of 1536 nm emission of Er doped ZnO nanopowder by Ag doping - Zamiri, Reza
Er, Er-Ag and Er-Mg co-doped ZnO nanopowders were prepared by wet chemical precipitation method. The structure and morphology of the prepared samples were studied by XRD and SEM, respectively. The effect of Ag and Mg on visible and IR emission properties of Er doped ZnO nanopowders have been systematically investigated. We found that Mg did not change the visible and IR emission properties of Er doped ZnO nanopowders. But, addition of Ag drastically decreases the visible emission and enhances the IR emission at 1536 nm. (C) 2014 Elsevier B.V. All rights reserved.